The use of the thermographic examination in non-specific low back pain in elderly: controlled study - Xavier, Gabriela Santos; Barbosa, Danillo; Batista, Mariane Pereira; Ferreira, Mônica Beatriz; Kerppers, Ivo IIvan; Foresti, Bruno Bonfim (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Chronic low back pain (CLBP) affects an important part of the population worldwide and contributes to increased spending on medicines and imaging tests. An alternative in the diagnosis of nonspecific CLBP is the thermography examination, since it has low cost, good sensitivity and specificity in inflammatory processes. Objectives: The present article aimed to evaluate non - specific CLBP in elderly patients using thermography (TermoScanTD200) and the instrument of inability of Oswestry. Methods: The study included 120 subjects with a mean age of ±78.8 years. Results: the results of the column disability assessment reported that 60% of the sample reported moderate disability and 3% of the sample reported disability. In the thermography examination, 40% of the sample presented alterations in the lumbar 5 (L5), 20% showed changes in lumbar 3 (L3) and lumbar 4 (L4) and 10% of the sample presented changes in lumbar 1 (L1) and lumbar 2 (L2). When comparing lumbar spine follow-up with type of inflammatory process, it was observed that 40% of the sample presented a prevalence of acute inflammatory process in the lumbar 5 (L5), and 30% of the sample presented a prevalence of sub-acute inflammatory process in lumbar 3 (L3) and 40% of the sample presented a prevalence of chronic inflammatory process in lumbar 5 (L5). Conclusion: In view of the above, it is suggested that the thermography examination is an important tool in the diagnosis of nonspecific low back pain in the elderly.